Sexually transmitted diseases in Italy: clinical returns versus statutory notifications. Issue 5 (October 1990) - Greco, D; Giuliani, M; Suligoi, B; Panatta, M; Giannetti, A
Abstract : Sexually Transmitted Diseases (STD) surveillance has caught the attention of the Italian public health authorities during the past decades. The spread of HIV infection increased the awareness of the need for a better STD surveillance system. This paper reports a retrospective survey of STD clinics in Italy, intended to form an epidemiological base for further development of STD surveillance. The data for 1986-87 and 1988 on a predefined set of diseases, all of them sexually transmitted, were collected from 85 of 127 centres contacted. The data obtained offer the first national figures for some STD not included in the statutory notification list, such as chlamydial infection, herpes and genital warts, as well as HIV infections. Those data show an increase in time frequencies. For gonorrhoea and syphilis, it was possible to compare our data with statutory notifications, showing a large gap between notified and reported cases. This gap is not stable in time (increasing in time) or in geographical area (increasing from north to south).